PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE ENVIRONMENTAL DISCLOSURE TERHADAP NILAI PERUSAHAAN BUMN PERIODE 2012-2014 - APRILLY YANTI, AYU (Jurnal Akuntansi AKUNESA, 2015)
The aim in this research was to examine the influence of Good Corporate Governance and Corporate Environmental Disclosure on SOE’s Firm Value of period 2012-2014. This study uses secondary data and multiple regression analysis method. The sample was 44 SOE’s enterprises listed on the Indonesia Stock Exchange. These results indicate that the mechanism of Good Corporate Governance (Independent Commissioner, size of the Board of Directors, Managerial Ownership, Institutional Ownership, Audit Committee) and Corporate Environmental Disclosure does not significantly influence the Firm's value as measured by Tobins Q.Keywords: Good Corporate Governance, Corporate Environmental Disclosure, Firm’s Value